2-(Diphenylphosphino)benzoate-functionalized diiron ethane-1, 2-dithiolate complexes with uncoordinated or coordinated phosphine ligand. (1st September 2020) - Yan, Lin; Wang, Ling-Hui; Li, Xie; Li, Ao; Xiao, Qi-Min; Liu, Xu-Feng; Li, Yu-Long; Liu, Xing-Hai; Jiang, Zhong-Qing
Abstract: Treatment of the starting complex [Fe2 (CO)6 { μ -SCH2 CH(CH2 OH)S}] (1 ) with 2-(diphenylphosphino)benzoic acid in the presence of N, N '-dicyclohexylcarbodiimide and 4-dimethylaminopyridine gave the corresponding ester derivative [Fe2 (CO)6 { μ -SCH2 CH(CH2 O2 CC6 H4 PPh2 -2)S}] (2 ) in 92% yield. Further treatment of complex 2 with one equivalent of Me3 NO · 2 H2 O as the decarbonylating agent yielded diphenylphosphino-substituted complex [Fe2 (CO)5 { μ -SCH2 CH(CH2 O2 CC6 H4 PPh2 -2)S}] (3 ) in 79% yield. Both complexes were characterized by elemental analysis, spectroscopy, as well as by X-ray crystallography. Additionally, the electrochemical properties of these complexes were studied by cyclic voltammetry. Graphical Abstract: uf0001